The GABAА receptors agonists and antagonists influence on formation of a latent inhibition at rats with different levels of anxiety - A. V. Redkina; L. V. Loskutova; Т. A. Zamoshchina (Бюллетень сибирской медицины)
Latent inhibition phenomenon indexes the ability to ignore irrelevant stimuli. Disturbance of latent inhibition is registered in different psychiatric populations with pathology in the emotional and cognitive spheres. In our experiments latent inhibition was measured in a conditioned passive avoidance reaction in rats that previously received 0 or 20 conditioned stimuli exposures followed by foot shock. Latent inhibition was disrupted in high-anxiety rats and pathologically enhanced in low-anxiety rats. The effects of an agonist (muscimol) and an antagonist (biсuсulline) of GABAA receptors on the learning and latent inhibition in these rats were studied. In high-anxiety rats, muscimol (1 mg/kg) had no effect on learning but enhanced latent inhibition. Biсuсulline (1 mg/kg) enhanced both acquisition of the reflex and latent inhibition in low-anxiety rats. The present results show direct involvement of GABAA-receptors in process of attentional inhibition to irrelevant information.